Estrogen regulation of the transient outward K+ current involves estrogen receptor α in mouse heart. (September 2015) - El Gebeily, Gracia; El Khoury, Nabil; Mathieu, Sophie; Brouillette, Judith; Fiset, Céline
Abstract: Background and objective: We have previously shown that androgens upregulate cardiac K + channels and shorten repolarization. However, the effects that estrogens (E2 ) and estrogen receptors (ER) might have on the various repolarizing K + currents and underlying ion channels remain incompletely understood. Accordingly, our objective was to verify whether and how E2 and its ERs subtypes influence these K + currents. Methods and results: In order to examine the influence of E2 and ERs on K + currents we drastically lowered the E2 level through ovariectomy (OVX; 74% reduction vs CTL) and in parallel, we used female mice lacking either ERα (ERαKO) or ERβ (ERβKO). In OVX mice, results showed a specific increase of 35% in the density of the Ca 2 + -independent transient outward K + current (Ito ) compared to CTL. Western blots showed increase in Kv4.2 and Kv4.3 sarcolemmal protein expression while qPCR revealed higher mRNA expression of only Kv4.3 in OVX mice. This upregulation of Ito was correlated with a shorter ventricular action potential duration and QTc interval. In ERαKO but not ERβKO mice, the mRNA of Kv4.3 was selectively increased. Furthermore, when ventricular myocytes obtained from ERαKO and ERβKO were cultured in the presence of E2, results showed that E2 reduced Ito density only in ERβKO myocytes confirming the repressive role of E2 -ERα in regulating Ito . Conclusion: Altogether, these results suggest that E2 negatively regulates the density of Ito through ERα, this highlights a potential role for this female hormone and its α-subtype receptor in modulating cardiac electrical activity. Highlights: The role of E2 in regulating ion channels involved in repolarization remains incompletely understood. Reduction of E2 through ovariectomy led to a specific increase in the density of Ito . The increase in Ito was attributable to a Kv4.2 and Kv4.3 protein upregulation. Transcriptional and post-transcriptional mechanisms regulate Kv4.3 and Kv4.2 respectively. ERα and ERβ knock-out mice revealed that ERα has repressive role in regulating Kv4.3 and Ito .